Early Childhood Teacher's Ability to Implement Independent Curriculum at State Kindergarten Duren Sawit 02 Pondok Bambu - Wirastri Setyorini; Lilis Suryani (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This research aims to examine the ability of PAUD teachers to implement the Independent Curriculum at Duren Sawit 02 Pondok Bambu State Kindergarten, over a period of 3 months, namely September-December 2023. Based on its type, this research is descriptive qualitative research. The data collection method in this research uses three models: interviews, observation and documentation. The data obtained is valid and has a degree of trust, so researchers use two techniques: diligent observation and data triangulation. The data analysis technique used is the Miles and Huberman method which consists of data collection, data reduction, data presentation and conclusion drawing. The results of this research show that teachers have been able to implement the Independent Curriculum by implementing project-based learning, formative assessments, summative assessments, portfolios and performance-based assessments, as well as creating teaching modules that suit children's interests and talents well.